(untitled) (Sciences & Technology. A, exactes sciences, 2016)
The present study concerns thevibrationofa pipetransportingfluid(internal fluid) withaconstant flow rate.The fluidflowing in the pipehas the samemovementas that of theinflectionalstructure; it creates an interaction «fluid-structure" which results ina decrease inrigidity anddampingbehaviorof the structure pipe-fluid. A theoretical studywas conductedforthe establishmentofkineticenergyand deformationof the system(fluid, structure) needed todetermination ofequations of motionin matrix form.Modelingofsolid-liquidwas conducted byp version of the finite element method. A program is developed and validated; comparing the results with those found in the literature is made. This allowed us to study the influence of physical and geometrical parametersof thecoupled structure.Amongthese parameterswe quotethe flow velocity, density, elastic modulus, the length of pipeandboundary condition.